Structuralism in the Process and Events Toward the Constitutional Court Decision No.90/PUU-XXI/2023: The Relevance of Islamic Siyasah - Rahmi, Melvi; Rozi, Syafwan; Helfi, Helfi (GIC Proceeding, 2024)
The Constitutional Court granted that the age limit for presidential and vice presidential candidates is 40 years old, unless they have experience as regional heads. This is stated in Constitutional Court Decision Number 90/PUU-XXI/2023. Constitutional change is one of the applications of the basic structure theory of structuralism to the field of law. State administration is the meaning of siyasah or politics in Islam. By definition, Islamic Siyasah is creating benefits for the people by guiding them to the path of salvation. Therefore, this research will discuss, how is the theory of structuralism in the birth of Constitutional Court decision No. 90/PUU-XXI/2023? And how is the view of Islamic Siyasah against structuralism in the birth of the decision? This research is a library research that uses Munir Fuady's book entitled Theories in Legal Sociology and the journal Between Justice and Political Ethics: The Constitutional Court and the Age Limit for Presidential Candidates in Axiological Perspective by Viedini et al as the primary data source. Related references as secondary data sources. The data collected will then be presented using the descriptive analysis method. The results of this study show that structuralism is an understanding that states that humans are bound by structure. In issuing this decision, the Constitutional Court is bound by the legal language structure of Article 6 paragraph 2 of the 1945 Constitution. The Constitutional Court's efforts to realize dynamism and provide benefits in its decisions are in accordance with two Islamic siyasah rules. In Islamic siyasah as well, the interpretation of general texts or texts that require legal interpretation is the authority of the sulthah qadha'iyyah